Whale barnacles exaptational access to a forbidden paradise - Seilacher, Adolf 1925-2014 (2005)
Of all sessile filtrators, only some species of acorn barnacles managed to permanently settle on whales. Their key exaptation was probably a kind of biochemical cleaning process, which could be modified to penetrate into the host's dead cutis. Anchorage was further increased by coring prongs out of the whale skin (Coronula) or by transforming the wall into a cylindrical tube that added new rings at the base, while old ones flaked off at the surface in tandem with skin shedding (Tubicinella). Xenobalanus even everted its naked body into a stalked structure and reduced the wall plates to a minute, but highly efficient, anchor. Cryptolepas combines the strategies of Tubicinella and Coronula, but with a different structure of the radial folds. Because of a shared exaptational inventory, it is impossible to unravel phylogenetic relationships within the Coronulida from skeletal morphology alone.